2001
DOI: 10.4037/ajcc2001.10.4.238
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions and responses to procedural pain: results from Thunder Project II

Abstract: BACKGROUND: Little is known about the painfulness of procedures commonly performed in acute and critical care settings. OBJECTIVE: To describe pain associated with turning, wound drain removal, tracheal suctioning, femoral catheter removal, placement of a central venous catheter, and nonburn wound dressing change and frequency of use of analgesics during procedures. METHODS: A comparative, descriptive design was used. Numeric rating scales were used to measure pain intensity and procedural distress; word lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(154 citation statements)
references
References 0 publications
4
142
1
7
Order By: Relevance
“…[3][4][5][6][7] The most painful procedure reported by about 6000 acute and critically ill adult patients in the US Thunder II study was being turned. 1 This was supported in a recent Australian study where results from 61 conscious ICU patients indicated that postural change was one of the routine procedures causing pain. 8 This activity happens every 2-3 h in most ICU, thus it is likely experienced by a significant proportion of ICU patients on a daily basis.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…[3][4][5][6][7] The most painful procedure reported by about 6000 acute and critically ill adult patients in the US Thunder II study was being turned. 1 This was supported in a recent Australian study where results from 61 conscious ICU patients indicated that postural change was one of the routine procedures causing pain. 8 This activity happens every 2-3 h in most ICU, thus it is likely experienced by a significant proportion of ICU patients on a daily basis.…”
Section: Introductionmentioning
confidence: 73%
“…NRS correlate well with Likert-type measures of pain intensity from 0.65 to 0.88 18 and are easy to administer and score and produce higher rates of correct responses. 11 Puntillo et al 1 used NRS in their large Thunder II study and report that construct and concurrent validities have been established.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, surveys of pain among these departments focus on procedures known as potentially painful. Other studies have thoroughly described the pain related to a few specific procedures (Puntillo et al, 2001(Puntillo et al, , 2002Li and Puntillo, 2004;Gelinas et al, 2004). Except in those situations, little scientific information is currently available about painful procedures or about the intensity or frequency of the pain they cause.…”
Section: Introductionmentioning
confidence: 99%